The Effect of Water on the 2‐Propanol Oxidation Activity of Co‐Substituted LaFe1−CoxO3 Perovskites. Issue 68 (8th November 2021) - Dreyer, Maik; Cruz, Daniel; Hagemann, Ulrich; Zeller, Patrick; Heidelmann, Markus; Salamon, Soma; Landers, Joachim; Rabe, Anna; Ortega, Klaus Friedel; Najafishirtari, Sharif; Wende, Heiko; Hartmann, Nils; et al.
Abstract: Perovskites are interesting oxidation catalysts due to their chemical flexibility enabling the tuning of several properties. In this work, we synthesized LaFe1−x Cox O3 catalysts by co‐precipitation and thermal decomposition, characterized them thoroughly and studied their 2‐propanol oxidation activity under dry and wet conditions to bridge the knowledge gap between gas and liquid phase reactions. Transient tests showed a highly active, unstable low‐temperature (LT) reaction channel in conversion profiles and a stable, less‐active high‐temperature (HT) channel. Cobalt incorporation had a positive effect on the activity. The effect of water was negative on the LT channel, whereas the HT channel activity was boosted for x>0.15. The boost may originate from a slower deactivation rate of the Co 3+ sites under wet conditions and a higher amount of hydroxide species on the surface comparing wet to dry feeds. Water addition resulted in a slower deactivation for Co‐rich catalysts and higher activity in the HT channel state. Abstract : The effect of water addition on 2‐propanol oxidation was studied on LaFe1‐x Cox O3 catalysts. After surpassing a Co content threshold (x=0.15) the effect of water on the activity at elevated temperatures is beneficial due to slower Co 3+ reduction and the number of hydroxide species on the catalyst surface increased.